MANAGEMENT ACCOUNTING IN THE MANAGEMENT SYSTEM - Hafiza Farhodovna Gulboyeva; Bakhtiyor Razzoqovich Bahronov (International Journal of Literature and Language Studies, 2026)
Abstract This paper explores the multidimensional role of management accounting as an indispensable internal subsystem within the broader organizational management and control infrastructure. In today’s highly volatile and competitive corporate environment, organizations require sophisticated mechanisms to transform raw operational data into strategic business intelligence. Unlike financial accounting, which primarily addresses external compliance and historical reporting, management accounting is inherently future-oriented, adaptive, and tailored to the explicit needs of internal leadership. Operating across three primary functional pillars—planning and budgeting, control and performance evaluation, and strategic decision-making—this discipline bridges the gap between executive vision and operational reality. By examining critical methodologies such as Cost-Volume-Profit (CVP) analysis, capital budgeting, variance analysis, Responsibility Accounting, Activity-Based Costing (ABC), Relevant Costing, and the Balanced Scorecard (BSC), the study demonstrates how contemporary management accounting functions as the primary engine for resource optimization, corporate accountability, managerial agility, and long-term organizational sustainability.